Pengaruh Model Problem Based Learning Berbantuan Media PhET terhadap Hasil Belajar Fisika Siswa Kelas XI - Siti Jamila; Ni Nyoman Sri Putu Verawati; Makhrus Makhrus (-, 2023)
This study aims to determine the effect of the Problem Based Learning model assisted by PhET media on the physics learning outcomes of class XI students. This type of research is a quasi-experimental research design with nonequivalent control group design. The population of this study were all students of class XI SMA Negeri 6 Mataram, totaling four classes. The sample of this study was class XI IPA 1 as the experimental class and class XI IPA 3 as the control class which were selected using the Purposive Sumpling technique. The results of study showed that there was an influence of the PhET media-assisted Problem Based Learning moddel on the physics learning outcomes of class XI students.